PERAN PENULIS NASKAH DALAM FILM DOKUMENTER "JERAT DILEMA: KONFLIK PEREMPUAN BERPERAN GANDA" - Allya Allysa Wongso, (2023)
Scriptwriters in documentary films have an important role, including developing ideas and themes into a film treatment which then becomes a story concept and film scenario. This research aims to provide education to the public in the form of a documentary film about women's conflicts with multiple roles and to change the negative stigma in society through the #WeSupportWomen campaign so that people show their support for women with multiple roles. In this expository documentary film with the theme of education about the dual roles of women, the script was written after conducting data research and field research, then the results of this research were made into a film treatment that was conceptualized in a structured manner using a three-action structure. This documentary film presents facts about the lives of women with multiple roles in the capital city and displays the conflicts they experience as housewives as well as female workers as well as providing educational exposure on how to live for them as well as solutions suggested by expert leaders for women with multiple roles. The end result of this research is the discovery of conflicts experienced by female informants who play multiple roles, including conflicts that occur because of time, tension, and the habit of carrying out one role intersects with carrying out another role. Female informants who play multiple roles tend to show an attitude of accepting the situation, and try to make peace with all the problems they face for the sake of their children.